(untitled) (Journal of Dhaka National Medical College & Hospital, 2019)
Background: Post dural puncture headache (PDPH) is a common complication of spinal anaesthesia. Median and paramedian approaches are used for spinal anaesthesia. Incidences of PDPH is more common among parturients due to hormonal effect leading to thining of Ligamentum Flavum. Objectives: To compare the incidence of post dural puncture headache in parturients undergoing caesarean section under spinal anaesthesia using median and paramedian approaches. Materials & Methods: This was a prospective, observational study, carried among 60 parturients undergo caesarean section under spinal anaesthesia at Dhaka National Medical Institute Hospital, Dhaka from May 2018 to April 2019. Patients were randomly allocated into two equal groups of thirty patients each, where Group M received spinal anaesthesia with median approach and Group P received spinal anaesthesia with paramedian approach. Incidence of PDPH, intensity of headache, complication of PDPH (nausea, vomiting, coughing) for a period of 3 days postoperatively. Haemodynamic parameters, heart rate, systolic and diastolic blood pressure were recorded for 10 minutes interval during operative procedure. Results: Among 30 patients of Group M, mean age was 26.53 ± 5.9 years, height was 151.27 ± 3.8 cm and weight was 63.77± 9.5 kg, while in Group P mean age was 27.00 ± 6.2 years, height was 152.10 ± 4.7 cm and weight 62.97± 9.1 kg. In median approach (Group M), 2 patients (6.6%) had PDPH; whereas in paramedian approach (Group P), 3 patients (10%) had PDPH and the difference was statistically insignificant (P-value-0.64). Regarding other complications, in Group M, 3 patients (10%) developed nausea, while in Group P, 4 patients (13.33%) complained nausea. 1 patient (3.33%) in Group M had vomiting, while 2 patients (6.67%) had vomiting in Group P. But the difference was not significant statistically. Conclusion: There is no statistically significant difference regarding the incidence of PDPH between median and paramedian approach among parturients undergoing caesarean section. J. Dhaka National Med. Coll. Hos. 2019; 25 (02): 10-14